# Theory Boolean_Algebra

theory Boolean_Algebra
imports Main
```(*  Title:      HOL/Library/Boolean_Algebra.thy
Author:     Brian Huffman
*)

section ‹Boolean Algebras›

theory Boolean_Algebra
imports Main
begin

locale boolean =
fixes conj :: "'a ⇒ 'a ⇒ 'a"  (infixr "⊓" 70)
and disj :: "'a ⇒ 'a ⇒ 'a"  (infixr "⊔" 65)
and compl :: "'a ⇒ 'a"  ("∼ _" [81] 80)
and zero :: "'a"  ("𝟬")
and one  :: "'a"  ("𝟭")
assumes conj_assoc: "(x ⊓ y) ⊓ z = x ⊓ (y ⊓ z)"
and disj_assoc: "(x ⊔ y) ⊔ z = x ⊔ (y ⊔ z)"
and conj_commute: "x ⊓ y = y ⊓ x"
and disj_commute: "x ⊔ y = y ⊔ x"
and conj_disj_distrib: "x ⊓ (y ⊔ z) = (x ⊓ y) ⊔ (x ⊓ z)"
and disj_conj_distrib: "x ⊔ (y ⊓ z) = (x ⊔ y) ⊓ (x ⊔ z)"
and conj_one_right [simp]: "x ⊓ 𝟭 = x"
and disj_zero_right [simp]: "x ⊔ 𝟬 = x"
and conj_cancel_right [simp]: "x ⊓ ∼ x = 𝟬"
and disj_cancel_right [simp]: "x ⊔ ∼ x = 𝟭"
begin

sublocale conj: abel_semigroup conj
by standard (fact conj_assoc conj_commute)+

sublocale disj: abel_semigroup disj
by standard (fact disj_assoc disj_commute)+

lemmas conj_left_commute = conj.left_commute
lemmas disj_left_commute = disj.left_commute

lemmas conj_ac = conj.assoc conj.commute conj.left_commute
lemmas disj_ac = disj.assoc disj.commute disj.left_commute

lemma dual: "boolean disj conj compl one zero"
apply (rule boolean.intro)
apply (rule disj_assoc)
apply (rule conj_assoc)
apply (rule disj_commute)
apply (rule conj_commute)
apply (rule disj_conj_distrib)
apply (rule conj_disj_distrib)
apply (rule disj_zero_right)
apply (rule conj_one_right)
apply (rule disj_cancel_right)
apply (rule conj_cancel_right)
done

subsection ‹Complement›

lemma complement_unique:
assumes 1: "a ⊓ x = 𝟬"
assumes 2: "a ⊔ x = 𝟭"
assumes 3: "a ⊓ y = 𝟬"
assumes 4: "a ⊔ y = 𝟭"
shows "x = y"
proof -
from 1 3 have "(a ⊓ x) ⊔ (x ⊓ y) = (a ⊓ y) ⊔ (x ⊓ y)"
by simp
then have "(x ⊓ a) ⊔ (x ⊓ y) = (y ⊓ a) ⊔ (y ⊓ x)"
then have "x ⊓ (a ⊔ y) = y ⊓ (a ⊔ x)"
with 2 4 have "x ⊓ 𝟭 = y ⊓ 𝟭"
by simp
then show "x = y"
by simp
qed

lemma compl_unique: "x ⊓ y = 𝟬 ⟹ x ⊔ y = 𝟭 ⟹ ∼ x = y"
by (rule complement_unique [OF conj_cancel_right disj_cancel_right])

lemma double_compl [simp]: "∼ (∼ x) = x"
proof (rule compl_unique)
show "∼ x ⊓ x = 𝟬"
by (simp only: conj_cancel_right conj_commute)
show "∼ x ⊔ x = 𝟭"
by (simp only: disj_cancel_right disj_commute)
qed

lemma compl_eq_compl_iff [simp]: "∼ x = ∼ y ⟷ x = y"
by (rule inj_eq [OF inj_on_inverseI]) (rule double_compl)

subsection ‹Conjunction›

lemma conj_absorb [simp]: "x ⊓ x = x"
proof -
have "x ⊓ x = (x ⊓ x) ⊔ 𝟬"
by simp
also have "… = (x ⊓ x) ⊔ (x ⊓ ∼ x)"
by simp
also have "… = x ⊓ (x ⊔ ∼ x)"
by (simp only: conj_disj_distrib)
also have "… = x ⊓ 𝟭"
by simp
also have "… = x"
by simp
finally show ?thesis .
qed

lemma conj_zero_right [simp]: "x ⊓ 𝟬 = 𝟬"
proof -
from conj_cancel_right have "x ⊓ 𝟬 = x ⊓ (x ⊓ ∼ x)"
by simp
also from conj_assoc have "… = (x ⊓ x) ⊓ ∼ x"
by (simp only:)
also from conj_absorb have "… = x ⊓ ∼ x"
by simp
also have "… = 𝟬"
by simp
finally show ?thesis .
qed

lemma compl_one [simp]: "∼ 𝟭 = 𝟬"
by (rule compl_unique [OF conj_zero_right disj_zero_right])

lemma conj_zero_left [simp]: "𝟬 ⊓ x = 𝟬"
by (subst conj_commute) (rule conj_zero_right)

lemma conj_one_left [simp]: "𝟭 ⊓ x = x"
by (subst conj_commute) (rule conj_one_right)

lemma conj_cancel_left [simp]: "∼ x ⊓ x = 𝟬"
by (subst conj_commute) (rule conj_cancel_right)

lemma conj_left_absorb [simp]: "x ⊓ (x ⊓ y) = x ⊓ y"
by (simp only: conj_assoc [symmetric] conj_absorb)

lemma conj_disj_distrib2: "(y ⊔ z) ⊓ x = (y ⊓ x) ⊔ (z ⊓ x)"
by (simp only: conj_commute conj_disj_distrib)

lemmas conj_disj_distribs = conj_disj_distrib conj_disj_distrib2

subsection ‹Disjunction›

lemma disj_absorb [simp]: "x ⊔ x = x"
by (rule boolean.conj_absorb [OF dual])

lemma disj_one_right [simp]: "x ⊔ 𝟭 = 𝟭"
by (rule boolean.conj_zero_right [OF dual])

lemma compl_zero [simp]: "∼ 𝟬 = 𝟭"
by (rule boolean.compl_one [OF dual])

lemma disj_zero_left [simp]: "𝟬 ⊔ x = x"
by (rule boolean.conj_one_left [OF dual])

lemma disj_one_left [simp]: "𝟭 ⊔ x = 𝟭"
by (rule boolean.conj_zero_left [OF dual])

lemma disj_cancel_left [simp]: "∼ x ⊔ x = 𝟭"
by (rule boolean.conj_cancel_left [OF dual])

lemma disj_left_absorb [simp]: "x ⊔ (x ⊔ y) = x ⊔ y"
by (rule boolean.conj_left_absorb [OF dual])

lemma disj_conj_distrib2: "(y ⊓ z) ⊔ x = (y ⊔ x) ⊓ (z ⊔ x)"
by (rule boolean.conj_disj_distrib2 [OF dual])

lemmas disj_conj_distribs = disj_conj_distrib disj_conj_distrib2

subsection ‹De Morgan's Laws›

lemma de_Morgan_conj [simp]: "∼ (x ⊓ y) = ∼ x ⊔ ∼ y"
proof (rule compl_unique)
have "(x ⊓ y) ⊓ (∼ x ⊔ ∼ y) = ((x ⊓ y) ⊓ ∼ x) ⊔ ((x ⊓ y) ⊓ ∼ y)"
by (rule conj_disj_distrib)
also have "… = (y ⊓ (x ⊓ ∼ x)) ⊔ (x ⊓ (y ⊓ ∼ y))"
by (simp only: conj_ac)
finally show "(x ⊓ y) ⊓ (∼ x ⊔ ∼ y) = 𝟬"
by (simp only: conj_cancel_right conj_zero_right disj_zero_right)
next
have "(x ⊓ y) ⊔ (∼ x ⊔ ∼ y) = (x ⊔ (∼ x ⊔ ∼ y)) ⊓ (y ⊔ (∼ x ⊔ ∼ y))"
by (rule disj_conj_distrib2)
also have "… = (∼ y ⊔ (x ⊔ ∼ x)) ⊓ (∼ x ⊔ (y ⊔ ∼ y))"
by (simp only: disj_ac)
finally show "(x ⊓ y) ⊔ (∼ x ⊔ ∼ y) = 𝟭"
by (simp only: disj_cancel_right disj_one_right conj_one_right)
qed

lemma de_Morgan_disj [simp]: "∼ (x ⊔ y) = ∼ x ⊓ ∼ y"
by (rule boolean.de_Morgan_conj [OF dual])

end

subsection ‹Symmetric Difference›

locale boolean_xor = boolean +
fixes xor :: "'a ⇒ 'a ⇒ 'a"  (infixr "⊕" 65)
assumes xor_def: "x ⊕ y = (x ⊓ ∼ y) ⊔ (∼ x ⊓ y)"
begin

sublocale xor: abel_semigroup xor
proof
fix x y z :: 'a
let ?t = "(x ⊓ y ⊓ z) ⊔ (x ⊓ ∼ y ⊓ ∼ z) ⊔ (∼ x ⊓ y ⊓ ∼ z) ⊔ (∼ x ⊓ ∼ y ⊓ z)"
have "?t ⊔ (z ⊓ x ⊓ ∼ x) ⊔ (z ⊓ y ⊓ ∼ y) = ?t ⊔ (x ⊓ y ⊓ ∼ y) ⊔ (x ⊓ z ⊓ ∼ z)"
by (simp only: conj_cancel_right conj_zero_right)
then show "(x ⊕ y) ⊕ z = x ⊕ (y ⊕ z)"
by (simp only: xor_def de_Morgan_disj de_Morgan_conj double_compl)
(simp only: conj_disj_distribs conj_ac disj_ac)
show "x ⊕ y = y ⊕ x"
by (simp only: xor_def conj_commute disj_commute)
qed

lemmas xor_assoc = xor.assoc
lemmas xor_commute = xor.commute
lemmas xor_left_commute = xor.left_commute

lemmas xor_ac = xor.assoc xor.commute xor.left_commute

lemma xor_def2: "x ⊕ y = (x ⊔ y) ⊓ (∼ x ⊔ ∼ y)"
by (simp only: xor_def conj_disj_distribs disj_ac conj_ac conj_cancel_right disj_zero_left)

lemma xor_zero_right [simp]: "x ⊕ 𝟬 = x"
by (simp only: xor_def compl_zero conj_one_right conj_zero_right disj_zero_right)

lemma xor_zero_left [simp]: "𝟬 ⊕ x = x"
by (subst xor_commute) (rule xor_zero_right)

lemma xor_one_right [simp]: "x ⊕ 𝟭 = ∼ x"
by (simp only: xor_def compl_one conj_zero_right conj_one_right disj_zero_left)

lemma xor_one_left [simp]: "𝟭 ⊕ x = ∼ x"
by (subst xor_commute) (rule xor_one_right)

lemma xor_self [simp]: "x ⊕ x = 𝟬"
by (simp only: xor_def conj_cancel_right conj_cancel_left disj_zero_right)

lemma xor_left_self [simp]: "x ⊕ (x ⊕ y) = y"
by (simp only: xor_assoc [symmetric] xor_self xor_zero_left)

lemma xor_compl_left [simp]: "∼ x ⊕ y = ∼ (x ⊕ y)"
apply (simp only: xor_def de_Morgan_disj de_Morgan_conj double_compl)
apply (simp only: conj_disj_distribs)
apply (simp only: conj_cancel_right conj_cancel_left)
apply (simp only: disj_zero_left disj_zero_right)
apply (simp only: disj_ac conj_ac)
done

lemma xor_compl_right [simp]: "x ⊕ ∼ y = ∼ (x ⊕ y)"
apply (simp only: xor_def de_Morgan_disj de_Morgan_conj double_compl)
apply (simp only: conj_disj_distribs)
apply (simp only: conj_cancel_right conj_cancel_left)
apply (simp only: disj_zero_left disj_zero_right)
apply (simp only: disj_ac conj_ac)
done

lemma xor_cancel_right: "x ⊕ ∼ x = 𝟭"
by (simp only: xor_compl_right xor_self compl_zero)

lemma xor_cancel_left: "∼ x ⊕ x = 𝟭"
by (simp only: xor_compl_left xor_self compl_zero)

lemma conj_xor_distrib: "x ⊓ (y ⊕ z) = (x ⊓ y) ⊕ (x ⊓ z)"
proof -
have *: "(x ⊓ y ⊓ ∼ z) ⊔ (x ⊓ ∼ y ⊓ z) =
(y ⊓ x ⊓ ∼ x) ⊔ (z ⊓ x ⊓ ∼ x) ⊔ (x ⊓ y ⊓ ∼ z) ⊔ (x ⊓ ∼ y ⊓ z)"
by (simp only: conj_cancel_right conj_zero_right disj_zero_left)
then show "x ⊓ (y ⊕ z) = (x ⊓ y) ⊕ (x ⊓ z)"
by (simp (no_asm_use) only:
xor_def de_Morgan_disj de_Morgan_conj double_compl
conj_disj_distribs conj_ac disj_ac)
qed

lemma conj_xor_distrib2: "(y ⊕ z) ⊓ x = (y ⊓ x) ⊕ (z ⊓ x)"
proof -
have "x ⊓ (y ⊕ z) = (x ⊓ y) ⊕ (x ⊓ z)"
by (rule conj_xor_distrib)
then show "(y ⊕ z) ⊓ x = (y ⊓ x) ⊕ (z ⊓ x)"
by (simp only: conj_commute)
qed

lemmas conj_xor_distribs = conj_xor_distrib conj_xor_distrib2

end

end
```